Investigation on the Bond and Sukuk market in Malaysia - Alom, Shahedin; Khan , Mohammad Mehdi Hasan (South Asian Journal of Social Sciences and Humanities, 2022)
The Malaysian capital market has a dual full fledged Islamic bond (Sukuk) instrument which operates in parallel with the conventional bond. This study investigates the correlation between the return of Sukuk portfolio differ significantly from conventional bond in Malaysia capital market. For this purpose, we just used the TR BPAM ALL BOND INDEX series from 2008 to 2013. This study is using the paired sample T test and correlation analysis; it found a positive and significant correlation between the returns of the conventional bond and Islamic (Sukuk) bond between the short term maturity bonds comparatively. Interestingly, the individual results of two debt instrument found that there is a noteworthy difference in the mean among long-term maturity of Sukuk and conventional bonds efficiency, which indicates that such two financial products, while traded in the same marketplace, are performed in different ways. The evidence justifies that long term maturity bond and Sukuk indicate that the higher probability of volatility in return and the maturity of the portfolio of bond and Sukuk.